The common tangents to the circles and form a triangle which is
Note: Pick the best option.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
From the first equation:- x 2 + y 2 + 2 x = 0 ( x + 1 ) 2 + y 2 = 1 This is the equation of a circle of radius 1 centered at ( − 1 , 0 ) .
From second equation:- x 2 + y 2 − 6 x = 0 ( x − 3 ) 2 + y 2 = 9 This is the equation of a circle of radius 3 centered at ( 3 , 0 ) .
These two circles have 3 common tangents. One of them is y − a x i s and the other two are shown in the figure.
In the figure let E F = x and let ∠ A E F = θ .
Now in Δ A E D :- sin θ = 1 + x 1 … ( 1 ) In Δ B E C :- sin θ = 5 + x 3 … ( 2 ) From ( 1 ) and ( 2 ) 1 + x 1 = 5 + x 3 Simplifying above we get:- x = 1 Hence sin θ = 2 1 θ = 3 0 ∘ The figure has symmetry about x − a x i s . So we can say that the triangle so formed is equilateral.